Facile Preparation Route of Cellulose-Based Flame Retardant by Ball-Milling Mechanochemistry - Aaddouz, Mohamed; Laoutid, Fouad; Mariage, Jerome; Lazko, Jevgenij; Yada, Bopha; Mejdoubi, El Miloud; Toncheva, Antoniya; Dubois, Philippe (Molecules (Basel, Switzerland), 2024)
In this study, a sustainable cellulose-based flame-retardant additive was developed, characterized, and incorporated into polypropylene (PP). Microcrystalline cellulose (Cel) was chemically modified with P2O5 using the solvent-free ball-milling mechanochemistry approach at room temperature. This modification enabled phosphorus grafting onto cellulose, significantly enhancing the cellulose charring ability and improving the thermal stability of the char as revealed by thermogravimetric analysis (TGA). The resulting product, Cel-P, containing 4.15 wt.% phosphorus, was incorporated and uniformly dispersed as a flame-retardant (FR) additive at 30 wt.% in PP through melt processing. The PP+30-Cel-P composite demonstrated improved char formation and FR properties, including reduction of both peak heat release rate (pHRR) and total heat release (THR) in mass loss cone calorimetry (MLC). Moreover, lower light absorptivity was obtained by smoke opacity tests as compared to PP filled with unmodified cellulose.